Formulation mathématique de transfert de chaleur dans une poutre caisson de grande portée - MEZOUDJ GHAZEL (My University, 2010)
The aim of this research consists firstly in studying the different steps to design a cantilevered structure. Secondly heat transfer law is adapted in order to analyse the temperature distribution in a box-girder element. Finite difference method was used to solve heat equation, for different sections, in terms of time and depth. Then strains and stresses generated are also determined. Finally an analogical study between two-strata saturated fine soil consolidation and heat propagation in a cantilevered girder-box beam of a bridge.